Clinical and clinicopathological characteristics of acute lymphoblastic leukaemia in six cats. (31st August 2018) - Tomiyasu, H.; Doi, A.; Chambers, J. K.; Goto‐Koshino, Y.; Ohmi, A.; Ohno, K.; Tsujimoto, H.
Abstract : Objectives: To investigate the clinical characteristics of feline acute lymphoblastic leukaemia patients diagnosed according to the recent diagnostic criteria for the equivalent canine condition. Materials and Methods: The medical records of six cats diagnosed with acute lymphoblastic leukaemia were retrospectively reviewed to extract data on clinicopathological characteristics and outcomes. The lymphoid origin of the tumour cells was confirmed by polymerase chain reaction for antigen receptor gene rearrangement, flow cytometry or immunohistochemistry. Results: Non‐specific clinical signs such as lethargy and anorexia were common, and anaemia and thrombocytopenia were also commonly identified. Leucocytosis was observed in four cats and leucopenia was observed in two; the number of lymphoblasts in the peripheral blood samples varied among the cases. Lymphoblasts originated from B‐cell lineage in four cats and T‐cell lineage in one, and those of another cat were positive for both B‐cell marker CD21 and T‐cell marker CD8. Five of the six cats were treated with cytotoxic chemotherapy, and a partial response was obtained in two. The median overall survival was 55 days (range: 1 to 115). Clinical Significance: Acute lymphoblastic leukaemia should be considered if lymphoblasts are observed in peripheral blood, even if their number is small. The prognosis for cats that have acute lymphoblastic leukaemia is as poor as that for dogs, and further studies are needed to develop effective treatment.